Defect of zinc transporter ZRT1 ameliorates cadmium induced lipid accumulation in Saccharomyces cerevisiae. Issue 4 (21st March 2016) - Rajakumar, Selvaraj; Ravi, Chidambaram; Nachiappan, Vasanthi
Abstract : Cadmium (Cd) is a non-essential divalent heavy metal that enters the cells by utilizing the transport pathways of the essential metals, like zinc (Zn), in Saccharomyces cerevisiae . Abstract : Cadmium (Cd) is a non-essential divalent heavy metal that enters the cells by utilizing the transport pathways of the essential metals, like zinc (Zn), in Saccharomyces cerevisiae . This work focuses on Cd accumulation and its impact on deletion of Zn transporters Zrt1p and Zrt2p and lipid homeostasis. Cd exposure reduces the Zn levels in the mutant strains, and the effect was higher in zrt2 Δ cells. Upon Cd exposure, the wild-type and zrt2 Δ cells follow a similar pattern, but an opposite pattern was observed in zrt1 Δ cells. The Cd influx and ROS levels were high in both wild-type cells and zrt2 Δ cells but significantly reduced in zrt1 Δ cells. Cd exposure led to accumulation of triacylglycerol and lipid droplets in wild-type cells and zrt2 Δ cells but these levels were decreased in zrt1 Δ cells. Hence, these studies suggest that the zrt1 Δ cells provide resistance towards Cd and aid in the maintenance of lipid homeostasis in yeast cells.